(untitled) (Gayana Botánica, 2005)
Mitotic chromosome counts for Luzuriaga radicans Ruiz et Pav. and L. polyphylla (Hook) J.F. Macbr. from Chile, reported here for the first time, are the same as those reported for L. parviflora (Hook) Kunth in New Zealand and L. marginata (Gaertner) Benth. on Falkland Islands (2n = 2x = 20). These results indicate a constancy of chromosome number in the genus Luzuriaga.